Analysis Of Object Detection Method Of Histograms Oriented Gradients Device Sva - Meriani T; Cucus A (International Conference on Engineering and Technology Development (ICETD), 2017)
Condition of agriculture in Indonesia, now seemed quite alarming. Where Indonesia is known as an agricultural country (developed country agriculture), is now importing its staple food of othercountries. people and our beloved earth is still able to meet the needs of rice for our daily food. Notonly rice but other agricultural products also suffered the thereby. There is one way to address the issue of urban agriculture by means of applying the system of hydroponics (https://www.google.com)Hydroponics is a way to grow crops by using water without the use of soil , with an emphasis on meeting the needs of nutrients for plants in hydroponic needs less water than the water demand in thecultivation of the soil (https: //id.m.wikipedia.org/wiki/Hidroponik) Rarely urban communities have planted a hobby for many reasons as busy work, tired, lazy, and as his, so in this study made was thecontrol system and monitoring of hydroponic plants for people to be able to plant crops without having them involved directly on nutrition and others by just looking at their smart phones or throughthe website.